Exploring the antimicrobial potential from various parts of Ziziphus mauritiana Lam - Larbenno Pauloi; Rafidah Md Salim (Springer Nature, 2025)
Ziziphus mauritiana Lam., a tropical tree from the Rhamnaceae family, is valued for its nutritional benefits and traditional medicinal uses. This study assessed the antimicrobial activity of different plant parts which are leaves, roots, bark, stems, and fruits, against Escherichia coli and Fusarium solani using methanolic extracts at 1.0 mg/mL. Streptomycin (1.0 mg/mL) and 0.8% methanol served as positive and negative controls, respectively. Plant-derived antimicrobial agents are gaining attention for their bioavailability, safety, and low resistance potential. The methanolic extracts exhibited potent antimicrobial effects, with minimum bactericidal and fungicidal concentrations (MBC/MFC) of 0.8 mg/mL for E. coli and 1.0 mg/mL for F. solani. Leaf extracts showed the strongest inhibition, with zones of 101.47 mm² for E. coli and 88.11 mm² for F. solani, followed by root extracts (86.48 mm² against F. solani). The study supports Z. mauritiana’s potential in treating human diseases and underscores the need for sustainable conservation. The results also emphasize the need to conserve this underutilized species for future pharmacological applications.